Comparative morpho‐physiological aspects and transcriptomics of the gonads from wild caught and enhanced green sea urchin (Strongylocentrotus droebachiensis). Issue 1 (28th December 2021) - Sætra, I. Mathisen; Burgerhout, E.; Johnsen, H.; James, P.
Abstract: There is a growing interest in sea urchin roe enhancement around the world, but relatively little is known about the physical differences between enhanced and wild sea urchin roe and the causes of any differences. The main objective of this study was to compare various aspects of roe from wild and enhanced green sea urchin ( Strongylocentrotus droebachiensis) using morphological and histological examinations, as well as analyses of amino and fatty acids, and gene expression profiles. Sea urchins were collected ( n  = 250) from a wild population and held in raceways where they were fed a commercially available formulated diet for 14 weeks (mid‐August – mid‐November). At consecutive time‐points, samples from the wild and enhanced sea urchins were obtained. The gonad index (GI) increased significantly in the enhanced sea urchins from 6.1% to 29.65% at week 12, while no significant increase was recorded in wild sea urchins. The concentrations of the amino acids' glycine, lysine and leucine were different between the treatments, the first two being higher and the latter lower in the enhanced sea urchin roe. Wild sea urchins had 6% more unidentified fatty acid content than enhanced sea urchins. A significant progress in reproductive stages in wild sea urchins was observed; however, none in the enhanced sea urchins, suggesting gametogenesis is inhibited in captivity, or variations in feed availability. Enhanced sea urchins had relatively less reproductive cells and an overall messier and less uniform appearance mid‐trial (weeks 8–10). Scanning electron microscopy images showed less structured and greater number of surface flagella in enhanced sea urchins. Transcriptomic analysis by RNA‐sequencing showed a total of 255 differentially expressed genes between the wild and enhanced groups, which had functions largely involved in the biosynthesis of cholesterol and fatty acids, and ethanol degradation. Abstract : This study compared various aspects of roe from wild and enhanced green sea urchin ( Strongylocentrotus droebachiensis ) using morphological and histological examinations, as well as analyses of amino and fatty acids, and gene expression profiles. The results suggest that a rapid increase in GI may interrupt the structural integrity of the gonadal wall and transcriptomic analysis by RNA‐sequencing showed a total of 255 differentially expressed genes between the wild and enhanced groups.